2022
DOI: 10.1002/jrsm.1594
|View full text |Cite
|
Sign up to set email alerts
|

Robust Bayesian meta‐analysis: Model‐averaging across complementary publication bias adjustment methods

Abstract: Publication bias is a ubiquitous threat to the validity of meta-analysis and the accumulation of scientific evidence. In order to estimate and counteract the impact of publication bias, multiple methods have been developed; however, recent simulation studies have shown the methods' performance to depend on the true data generating process, and no method consistently outperforms the others across a wide range of conditions.Unfortunately, when different methods lead to contradicting conclusions, researchers can … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 99 publications
0
66
0
Order By: Relevance
“…. on heterogeneity, six weight functions and PET-PEESE publication-bias adjustment as specified in Bartoš, Maier, et al, 2021). We set the prior hypothesis probability to 0.50 for the effect size, heterogeneity, and publication bias.…”
Section: Example Reportmentioning
confidence: 99%
“…. on heterogeneity, six weight functions and PET-PEESE publication-bias adjustment as specified in Bartoš, Maier, et al, 2021). We set the prior hypothesis probability to 0.50 for the effect size, heterogeneity, and publication bias.…”
Section: Example Reportmentioning
confidence: 99%
“…Critically, our re-analysis addresses limitations in both previous meta-analyses. First, the analysis of enhanced expectancies fit only one bias correction model-the trim-and-fill method (Duval & Tweedie, 1998)-and that model has been shown to result in exaggerated effect size estimates and severely inflated Type 1 error rates in the presence of publication bias and small or null effects (Bartoš et al, 2022;Carter et al, 2019). Second, although the results from multiple reporting bias models coalesced around small effect sizes (ranged from g = -.11 to g = .26) in the analysis of self-controlled practice, there are no principled reasons for preferring one estimate over another.…”
Section: Regression Modelsmentioning
confidence: 99%
“…The self-controlled practice meta-data 2 , enhanced expectancy meta-data, and the combination of both the enhanced expectancy and self-controlled practice meta-data were analyzed with a z-curve. A z-curve analysis estimates the statistical power of all studies ever conducted within a given literature, even if those studies were not reported, on the basis of the significant results that are present (Bartoš et al, 2022). That power estimate is equivalent to the expected discovery rate, that is, the expected rate of significant results for a given literature.…”
Section: Z -Curvementioning
confidence: 99%
See 2 more Smart Citations